2021
DOI: 10.3390/ijerph18063251
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Health-Related Quality of Life in a Sample of Primary School Children: A Cross-Sectional Analysis

Abstract: Background: Health-related quality of life (HRQoL) in childhood is a multidimensional construct with many sub dimensions of subjective experience, including physical activity (PA), psychological well-being, social interaction, and school performance, that represents a fundamental health outcome to assess a child’s physical and psycho-social functioning. Our study aims to explore the potential predictors of children’s health-related quality of life, using a convenience sample from the Imola Active Break Study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
3
19
0
1
Order By: Relevance
“…Considering the activities that are not allowed, sports and other physical play were the first activities that seem to have been restricted. This type of play should be encouraged, considering the need to promote healthy lifestyles during childhood to prevent child obesity and a sedentary lifestyle [ 37 ], and promote HRQOL [ 38 ]. The evidence before the pandemic is clear in stating that children did not achieve the recommended daily amount of physical activity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the activities that are not allowed, sports and other physical play were the first activities that seem to have been restricted. This type of play should be encouraged, considering the need to promote healthy lifestyles during childhood to prevent child obesity and a sedentary lifestyle [ 37 ], and promote HRQOL [ 38 ]. The evidence before the pandemic is clear in stating that children did not achieve the recommended daily amount of physical activity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…En ese contexto, la obesidad y el sobrepeso son pro-blemas especialmente preocupantes durante la infancia y la adolescencia a nivel mundial 9 , y específicamente para Chile, dado que, según el Ministerio de Salud, la prevalencia de sobrepeso es 39,8% y de obesidad 31,2 % 10 . En consecuencia, al parecer las complicaciones relacionadas con el exceso de grasa corporal y el sedentarismo representan un importante problema de salud pública en diversos países y específicamente en Chile, por lo que estudiar el desempeño de la Apf en niños y adolescentes con adecuados y elevados niveles de masa grasa puede ser relevante, puesto que el exceso de grasa corporal se asocia a graves consecuencias sobre la salud 11 , bajos niveles de ApF 12,13 y un aumento significativo del riesgo de mortalidad prematura 14,15 .…”
Section: Introductionunclassified
“…Regarding physical activity volume, previous studies found that the higher the physical activity level, the higher the HRQoL [ 23 ]. Regarding physical activity intensity and improvement in HRQoL, a previous study showed that children who spent more time practicing moderate PA were associated with higher HRQoL scores [ 24 ]. In the same vein, a study that explore the commitment of physical activity recommendations found that meeting combinations of screen time with moderate-to-vigorous physical activity were related to higher HRQoL [ 25 ].…”
Section: Introductionmentioning
confidence: 99%